2016
DOI: 10.1172/jci.insight.87632
|View full text |Cite
|
Sign up to set email alerts
|

Soluble ADAM33 initiates airway remodeling to promote susceptibility for allergic asthma in early life

Abstract: Asthma is a chronic inflammatory airways disease that usually begins in early life and involves gene-environment interactions. Although most asthma exhibits allergic inflammation, many allergic individuals do not have asthma. Here, we report how the asthma gene a disintegrin and metalloprotease 33 (ADAM33) acts as local tissue susceptibility gene that promotes allergic asthma. We show that enzymatically active soluble ADAM33 (sADAM33) is increased in asthmatic airways and plays a role in airway remodeling, ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 50 publications
1
44
0
Order By: Relevance
“…To explore the biological role of ADAM33 / Adam33 in asthma progression, we have developed a series of mouse models 7 . We therefore set out to identify analogs of the human lead ASOs that could silence mouse Adam33 expression.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To explore the biological role of ADAM33 / Adam33 in asthma progression, we have developed a series of mouse models 7 . We therefore set out to identify analogs of the human lead ASOs that could silence mouse Adam33 expression.…”
Section: Resultsmentioning
confidence: 99%
“…Single-nucleotide polymorphisms in ADAM33 have been linked to asthma and bronchial hyperresponsiveness 4, 56, 7. Furthermore, in human embryonic lung explant culture, treatment with sADAM33 induces angiogenesis 8 and myogenesis, 7 pathological features of airway remodeling in asthma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ADAM33 belongs to a disintegrin and zinc‐dependent metalloprotease family and exhibits a complex organization that includes eight domains: signal sequence, prodomain, catalytic, disintegrin, cysteine rich, epidermal growth factor like, transmembrane, and cytoplasmic. A recent study revealed that in Adam33 ‐null mice, airway remodelling and inflammation after allergen challenge were both suppressed, suggesting an essential role of ADAM33 in asthma pathophysiology . Expression of ADAM33 is up‐regulated in airway smooth muscles, fibroblasts, and less frequently airway epithelium of patients with asthma.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanisms underlying these associations remain unknown; however, the soluble form of ADAM33 (sADAM33) may be involved. sADAM33, which is increased in bronchoalveolar fluid of patients with asthma, is efficiently released by transforming growth factor‐β 2 , is catalytically active, promotes angiogenesis in the human lung tissue, and induces airway remodelling, which may provide the “soil” for type‐2 inflammation and airway hyperresponsiveness . Potential interactions between ADAM33 and α catenin, an important protein in airway epithelial barrier function, may also contribute to susceptibility to asthma exacerbation.…”
Section: Discussionmentioning
confidence: 99%